Invasive alien plants : an ecological appraisal for the Indian subcontinent (CABI invasive species series ;, 2012)
This book consists of 24 chapters on invasive alien plants in India presented under the following headings: plant invasion in India (an overview); major invasive plants (part I); status, mapping and distribution (part II); environmental impact and risk assessment (part III); population dynamics and utilization (part IV); and management and legislation (part V). This book is the first in a series of publications that aims to address all topics relating to invasive species, including biosecurity surveillance, mapping and modelling, economics of invasive species and species interactions in plant invasions. Aimed at researchers, upper-level students and policy makers, titles in the series provide international coverage of topics related to invasive species, including both a synthesis of facts and discussions of future research perspectives and possible solutions.